Robotic Measurement and Control for Chiropractic Research - P. Goldsmith; S. Wynd; G. Kawchuk (Applied Bionics and Biomechanics)
The precision and programmability of robotic manipulators makes them suitable for biomechanics research, particularly when an experimental procedure must be accurately repeated multiple times. This paper describes a robotic system used to investigate biomechanical mechanisms of stroke in humans. A parallel robot manipulator is used to reproduce chiropractic manipulations on animal subjects using a 3-D vision system. An algorithm for calibrating the system is proposed and tested on the robot. An iterative learning control scheme is then introduced to improve positional accuracy. Experimental results demonstrate that the calibration procedure and learning scheme are both effective.